1981
DOI: 10.1002/ar.1092000316
|View full text |Cite
|
Sign up to set email alerts
|

A method for culturing canine tracheal smooth muscle cells in vitro: Morphologic and pharmacologic observations

Abstract: A method of culturing canine tracheal smooth muscle cells in vitro is described. The morphology of these cells is monitored up to 60 days in culture and selected stages are illustrated. The characteristics of these cells are numerous mechanical attachments, the presence of thick filaments in suitably processed cells, and their contractile response to in vitro administration of carbachol, a cholinomimetic drug. They also possess nexus formations and both thin (actin) filaments and 10-nm filaments. Mitosis is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…The ability of isolated or cultured smooth muscle cells to contract or relax in response to specific agonists is well documented [30,31] and airway smooth muscle cells are no exception. AVNER et al [32] reported that subconfluent primary cultures of canine tracheal smooth muscle cells contracted in response to the cholinomimetic, carbachol. Maintenance of this contractile phenotype in cultured smooth muscle cells is dependent upon a number of carefully controlled cell culture conditions, specifically cell density, avoidance of foetal bovine serum exposure and a requirement for heparin [14,33].…”
Section: Heterogeneity and Phenotypic Modulation Of Airway Smooth Musclementioning
confidence: 99%
“…The ability of isolated or cultured smooth muscle cells to contract or relax in response to specific agonists is well documented [30,31] and airway smooth muscle cells are no exception. AVNER et al [32] reported that subconfluent primary cultures of canine tracheal smooth muscle cells contracted in response to the cholinomimetic, carbachol. Maintenance of this contractile phenotype in cultured smooth muscle cells is dependent upon a number of carefully controlled cell culture conditions, specifically cell density, avoidance of foetal bovine serum exposure and a requirement for heparin [14,33].…”
Section: Heterogeneity and Phenotypic Modulation Of Airway Smooth Musclementioning
confidence: 99%
“…The techniques available for quantifying this muscle thickening can loosely be divided into in situ studies, involving morphometric analysis of the bronchial tree from normal and asthmatic patients [3][4][5][6][7], and studies employing cell culture techniques [17][18][19][20] as an in vitro model of the smooth muscle present in the intact airway wall.…”
Section: Airway Smooth Muscle Thickeningmentioning
confidence: 99%
“…This is compounded by modulations in phenotype, which may result in the loss of critical features of the differentiated cell. However, with the increasing realization of the role of smooth muscle in airway wall thickening and subsequent development of bronchial hyperresponsiveness, various groups have succeeded in culturing airway smooth muscle cells from a number of species, such as canine [17,18,27,28], bovine [29][30][31], rabbit [32][33][34], guinea-pig [35,36], sheep [37], and human [19,20,[38][39][40][41][42]. Although many of these initial concerns have been largely overcome, it remains essential to characterize fully the properties of these cells and to make comparisons where possible with the intact tissue.…”
Section: The Airway Smooth Muscle Cell In Culturementioning
confidence: 99%
See 2 more Smart Citations